Water Governance terhadap Optimalisasi Distribusi Air Bersih untuk Kebutuhan Masyarakat di Desa Lembur Kecamatan Kota Komba Kabupaten Manggarai Timur - Febriana Elwinda Fanyo; Hendrik Toda; David W. Rihi; Jacob Wadu (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This research is entitled Water Governance on Optimizing Clean Water Distribution to Meet Community Needs in Lembur Village, Komba City District, East Manggarai Regency. The purpose of this study is to find out the water governance process in Lembur Village. The method used in this study is a qualitative method. This study examines water governance on community needs using 3 important aspects, namely, the content layer, the institutional layer and the relationship layer. The results of the study show that the implementation of water governance in terms of the content layer is constrained in providing ineffective information, especially during the delivery of program work and policy making, officer training only occurs during National Programs such as PPIP and PAMSIMAS, while those managed by villages do not conduct training due to budget shortages, and policy strategies that are not optimal cause some people to not get clean water supply, but in the aspect of the institutional layer from the organizational side, there has been a division of roles and responsibilities, there is a strict structure and supervision, but there is a miscommunication between the overtime village government and clean water officers, even from the aspect of financing, budget realization that is not in line with the results in the field, then in the aspect of the relationship layer on the participation side, The community is not involved in the completion of clean water work and deliberately dismantles the pipes that have been worked. Financial alkalization and decision-making are not transparent and communication between the government and the community is not effective.